Hubungan Pengetahuan dan Sikap dengan Perilaku Mobilisasi Dini Pada Ibu Post Sectio Caesarea Di Ruang Rawat Gabung Kebidanan RSUD H Abdul Manap Kota Jambi - Bettywati E Tumanggor (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Early mobilization is a prominent factor in accelerating post-section cesarean recovery and can prevent post-section cesarean complications. The principle of early mobilization in post section Caesarea is carried out gradually and regularly followed by rest and adjusted to the client's physical condition. The purpose of this study was to determine the relationship between knowledge and attitudes with early mobilization behavior in post-section Caesarea mothers in the combined obstetrics ward at H. Abdul Manap Hospital Jambi City in 2018. The research method used descriptive research with a quantitative approach. The research design used cross-sectional. The sample in the study amounted to 40 people from the entire population of post-section Caesarea mothers who were treated in the combined obstetrics ward of RSUD H. Abdul Manap Jambi City in 2018. The sampling technique was accidental sampling. The univariate analysis aims to obtain an overview of the frequency distribution of each variable studied and bivariate analysis to analyze the relationship between knowledge and attitudes with early mobilization behavior post section Caesarea. Test analysis using chi-square statistical test. The results showed that from 23 respondents with good knowledge, 18 respondents (78.2%) with good early mobilization behavior, and five respondents (21.8%) with poor early mobilization behavior. Statistical test of the relationship of knowledge with early mobilization behavior obtained p-Value = 0.006 and OR = 7.00, meaning that there is a relationship between knowledge and early mobilization behavior in post-Sectio Caesarea. The results showed 31 respondents had good attitudes, 26 respondents (83.87%) with good early mobilization behavior, and five respondents (16.12%) with poor early mobilization behavior. The results of the statistical test of the relationship between attitudes and early mobilization behavior obtained p-value = 0.000 and OR = 22,235, meaning that there was a relationship between attitudes and early mobilization behavior in post-section Caesarea mothers.